Preferences of patients with chronic low back pain about nonsurgical treatments: Results of a discrete choice experiment. - Morillon, Gabin F.; Benkhalti, Maria; Dagenais, Pierre; Poder, Thomas G. (Health Expectations, 2023)
Introduction: This study aimed to assess patients' preferences of nonsurgical treatments for chronic low back pain (CLBP). Method: We conducted a discrete choice experiment (DCE) in Quebec, Canada, in 2018. Seven attributes were included: treatment modality, pain reduction, the onset of treatment efficacy, duration effectiveness, difficulties with daily activities, sleep problems, and knowledge of the patient's body and pain location. Treatment modalities were corticosteroid injections, supervised body‐mind physical activities, supervised sports physical activities, physical manipulations, self‐management courses, and psychotherapy. Utility levels were estimated using a logit model, a latent class model and a Bayesian hierarchical model. Results: Analyses were conducted on 424 $424$ individuals. According to the Bayesian hierarchical model, the conditional relative importance weights of attributes were as follows: (1) treatment modality (34.79%), (2) pain reduction (18.73%), (3) difficulties with daily activities (11.71%), (4) duration effectiveness (10.06%), (5) sleep problems (10.05%), (6) onset of treatment efficacy (8.60%) and (7) knowledge of the patient's body and pain location (6.06%). According to the latent class model that found six classes of respondents with different behaviours (using Akaike and Bayesian criteria), the treatment modality was the most important attribute for all classes, except for class 4 for which pain reduction was the most important. In addition, classes 2 and 5 refused corticosteroid injections, while psychotherapy was preferred only in class 3. Conclusion: Given the preference heterogeneity found in the analysis, it is important that patient preferences are discussed and considered by the physicians. This will help to improve the patient care pathway in a context of a patient‐centred model for a disease with growing prevalence. Patient or Public Contribution: A small group of patients was involved in the conception, design and interpretation of data. Participants in the DCE were all CLBP patients.